A look back at the origins of the Franco-African Summit: a new tool at the service of French African policy (1973-1981) - (:unkn) unknown (My University, 2022)
The first French-African heads of State summit occurred in 1973. Presented by the French and African leaders as a “Family reunion”, in regard of the close relations between France and the ancient members of the French Community. This first summit aimed to respond to a crisis climate due to the questioning of the cooperation system established by some of France’s partners in 1960. After Gorges Pompidou’s death and the election of Valery Giscard d’Estaing the 19th May 1974, the development of a new reunion in 1975 will allow the establishment of a yearly nature to the summit and the begging of an alternation dynamic for the hosting of the event between France and an African Country. The aim of this article is to study the evolution of the summit between its first happening in 1973 and the 8th edition in 1981. The French executive thoughts about the definition of the Summit, its expansion to new members and its institutionalization degree, allow one to grasp the evolution of French’s African policy objectives in relation to the national and international context.
Keywords: African Research